Facing the Threat of Modern Islamic State Insurgence to Increase National Resilience - Suharto Ladjide; Pujo Widodo; Resmanto Widodo Putro (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The threat of insurgency or modern rebellion of Islamic State in Indonesia is strongly influenced by the Southeast Asian regional environment which has a region with religious, ethnic, and cultural diversity. Ethnic, religious, racial, and intergroup conflicts have caused economic, political, and psychological losses. This article aims to describe and analyze using a variety of approaches applied in Indonesia to face the modern insurgency of the Islamic State using qualitative analysis methods. The technique of collecting data and information is through literature study. There are several jihadi organizations and groups that carry out operations, such as Jamaah Islamiyah, the Indonesian Mujahideen Council, and others. The vitality of radical and extremist groups is able to rise to renew leadership in the organizational network structure based on personal closeness, friendship, and family. National resilience as a dynamic condition of the nation and the conception of national development in achieving the goals and ideals of the nation, which is tough and tenacious and capable of developing national strength in dealing with all kinds and forms of threats, challenges, obstacles, and disturbances both coming from within and from within. outside, which threatens and endangers the integrity, identity and survival of the nation and state, especially the threat of modern Islamic State insurgency. Modern insurgency may never develop sufficient military strength to carry out conventional operations and must therefore rely on terrorism and psychological and political means. Therefore, facing the threat of the Islamic State, the Government of Indonesia must map the transformation of ISIS in Southeast Asia, especially in Indonesia, so that it is faced with proportional efforts and actions such as dealing with domestic insurgency, regional cooperation, and the involvement of extraregional forces within the ASEAN framework.